Overweight, Obesity and Psychological Correlates in a Moroccan Adolescent Sample - Fathi, Fatima; Choujaa, Hafsa; Abidli, Zakaria; Serhier, Zineb; Agoub, Mohamed; Saile, Rachid (Bangladesh Journal of Medical Science, 2024)
Background Over 18% of children and adolescents worldwide, aged 5-19 years old, are now considered overweight or obese. It is important to note that being overweight or obese can have a negative impact on the selfesteem and mental health of children and adolescents. Objectives The purpose of this study was to evaluate the levels of self-esteem, depression and their association with obesity/ overweight among a sample of Moroccan adolescents, aged between 12 and 17 years old. Method To achieve these aims, a cross-sectional survey was conducted, with a sample of students from 16 middle schools in Casablanca. The criteria for determining overweight and obesity were based on age and gender-specific BMI according to WHO reference standards. The Rosenberg Self-Esteem Scale was used to evaluate self-esteem, and the Beck Inventory for depression assessment. Results A sample of 410 adolescents consisted of 51.2% females and 55.1% participants aged between 13-15 years old. In the obesity category, girls had a significantly lower self-esteem score compared to boys. However, in the overweight category, although girls had a lower mean of self-esteem score compared to boys, there were no significant association in self-esteem scores based on Body Mass Index (BMI) categories and eating habits, specifically related to eating meals with family. Additionally, there was no association found between physical activity and self-esteem. However, a strong association was found between depression and both obesity/overweight and low self-esteem. Conclusion According to the results, when assessing the outcomes of obese adolescents, it is important to consider the variables of BMI, Rosenberg self-esteem scale, and depression. Therefore, it is recommended to implement psychological and psychiatric interventions in order to minimize these consequences. Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 798-807